Referee bias contributes to home advantage in English Premiership football - Boyko, R. H.; Boyko, A. R.; Boyko, M. G. (Journal of Sports Sciences, 2007)
Officiating bias is thought to contribute to home advantage. Recent research has shown that sports with subjective officiating tend to experience greater home advantage and that referees' decisions can be influenced by crowd noise, but little work has been done to examine whether individual referees vary in their home bias or whether biased decisions contribute to overall home advantage. We develop an ordinal regression model to determine whether various measures of home advantage are affected by the official for the match and by crowd size while controlling for team ability. We examine 5244 English Premier League (EPL) match results involving 50 referees and find that home bias differs between referees. Individual referees give significantly different levels of home advantage, measured as goal differential between the home and away teams, although the significance of this result depends on one referee with a particularly high home advantage (an outlier). Referees vary significantly and robustly in their yellow card and penalty differentials even excluding the outlier. These results confirm that referees are responsible for some of the observed home advantage in the EPL and suggest that home advantage is dependent on the subjective decisions of referees that vary between individuals. We hypothesize that individual referees respond differently to factors such as crowd noise and suggest further research looking at referees' psychological and behavioural responses to biased crowds.